Collective Perspective on Advances in Dyson-Schwinger Equation QCD - Bashir, Adnan; Chang Lei; Cloet, Ian C.; El-Bennich, Bruno [UNESP]; Liu Yu-Xin; Roberts, Craig D.; Tandy, Peter C. (Iop Publishing Ltd, 2012)
We survey contemporary studies of hadrons and strongly interacting quarks using QCD's Dyson-Schwinger equations,addressing the following aspects: confinement and dynamical chiral symmetry breaking; the hadron spectrum; hadron elastic and transition form factors, from small-to large-Q(2); parton distribution functions; the physics of hadrons containing one or more heavy quarks; and properties of the quark gluon plasma.
Keywords: confinement; dynamical chiral symmetry breaking; Dyson-Schwinger equations; hadron spectrum; hadron elastic and transition form factors; heavy mesons; in-hadron condensates; parton distribution functions; quark gluon plasma; U-A(1)-problem